2016
DOI: 10.3758/s13414-016-1061-3
|View full text |Cite
|
Sign up to set email alerts
|

Existence of competing modality dominances

Abstract: Approximately 40 years of research on modality dominance has shown that humans are inclined to focus on visual information when presented with compounded visual and auditory stimuli. The current paper reports a series of experiments showing evidence of both auditory and visual dominance effects. Using a behavioral oddball task, we found auditory dominance when examining response times to auditory and visual oddballs-simultaneously presenting pictures and sounds slowed down responses to visual but not auditory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
52
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 36 publications
1
52
0
Order By: Relevance
“…It is important to note that the reversal of dominance types demonstrated by Robinson et al [21] was the first reported example of auditory dominance in adults using this paradigm (see [20] for an example of auditory dominance in a modified n-back task). Given that it is not entirely clear what is driving some of the aforementioned findings, further examination of the stimulus factors influencing sensory dominance is critical to understanding this phenomenon.…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…It is important to note that the reversal of dominance types demonstrated by Robinson et al [21] was the first reported example of auditory dominance in adults using this paradigm (see [20] for an example of auditory dominance in a modified n-back task). Given that it is not entirely clear what is driving some of the aforementioned findings, further examination of the stimulus factors influencing sensory dominance is critical to understanding this phenomenon.…”
Section: Introductionmentioning
confidence: 81%
“…Therefore, it may seem that auditory dominance simply does not occur in adults unless precise and extreme experimental conditions are met (but see [15][16][17][18][19] for sensory dominance shifts from auditory to visual dominance during development). However, there are limited situations in which audition has been shown to dominate vision [20][21][22][23]. In a study conducted by Robinson and colleagues [21], participants monitored a stream of bimodal audiovisual stimuli and were instructed to press a key in response to any deviations from a standard (i.e., respond to a unimodal auditory oddball (only the tone changed), a unimodal visual oddball (only the picture changed), or a bimodal oddball (both the tone and the picture changed)).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations